AEROBIC GYMNASTICS WITHIN THE PHYSICAL EDUCATION CLASS FOR HIGHSCHOOL FEMALE STUDENTS ASPECTS REGARDING THE METHOD - Veronica BĂLTEANU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2011)
Physical education in school has included, in thepast few years, a decrease in the number of classes,even though specialists have warned regarding itsnegative consequences. The sedentariness,improper diet, and daily stress negatively influenceyoung people in the present and in a long-term. Inorder to prevent the further progress of thisphenomenon, physical education teachers do theirbest to make physical activities as pleasant aspossible, while keeping their benefits for the body,for a good health state, favouring physical harmonyby particularising their options. The study aims atcontributing in the favour of extending aerobicgymnastics within the physical education class,especially for highschool students. Using meansand structures specific to aerobic gymnastics,preferred by highschool female students,contributes at reaching the objectives of physicaleducation and at improving the work methodology.The results of the study reveal that making aschedule for the instruction in aerobic gymnastics,through a scientific approach of its contents andcourse, leads to optimal results (increased valuesfor the parameters evaluated). Also, we see the needof a special syllabus, taking into account students'theoretical and practical capabilities for aerobicgymnastics both during the physical education classand in their free time.